A Survey and Analysis of the Relationship between Human Resources Management and Organizational Performance - Hashemi, S. A.; Dehghanian, F. (Engineering, Technology & Applied Science Research, 2017)
This study aims to evaluate the relationship between human resources management and organizational performance with emphasis on the mediating role of organizational innovation. The study methodology is descriptive-correlation and structural equations modeling. The study population is employees of the electricity distribution company of Tehran city. The reliability and validity of measures were evaluated using Cronbach’s alpha and confirmatory analysis and the results showed the acceptable reliability and validity of measures. For data analysis, Pearson Correlation coefficient and structural equations method with Lisrel software were used. The results showed that the effect of organizational innovation mediating variable was indirectly 0.17 meaning that if human resources management is increased as 1%, the organization performance with the mediating role of organizational innovation is increased as 16%. This study evaluates the relationship between human resources management and organizational performance with emphasis on the mediating role of organizational innovation.